The Influence of Service Quality and Price on Consumer Satisfaction with Exo Tea Beverage Products in Galanggang Village RT 01 Batujajar District, West Bandung Regency - Hilda Apriliani; Moh. Aep Nurjamad (International Journal of Scientific Multidisciplinary Research, 2024)
The study was intended to test the impact of service quality and prices on consumer satisfaction for exo tea products in the village of galbaking, the district of bandung. The research method used is the quantitative method using data collection techniques through the distribution of the questionnaire to 174 respondents. A data analysis using a partial correlation test and simultaneous hypothetical test (f) indicates that the quality of service and price have significant impact on consumer satisfaction. The respondents in this study are mostly 15-25 years old and are dominated by men. The study contributed theoretically by applying marketing management theories and by providing practical Suggestions for the development of exo tea products